Evaluating The Suitability Of Euphrates River Water For Animal Consumption In The City Of Samawah Using The Canadian Catalyst: Evaluasi Kesesuaian Air Sungai Eufrat Untuk Konsumsi Ternak Di Kota Samawah Menggunakan Katalis Kanada - Kanbar, Tarteel Faisal Ghaze; Hasan, Mustafa Salah; Mohammed, Anmar Jasim (Procedia of Engineering and Life Science, 2025)
The study concluded that the assessment of the Euphrates River water quality in the Samawah area using the Canadian Water Quality Index (CWQI) and water quality standards for animal consumption showed variation in water quality among the studied sites. Site 1 (M1) was classified as "poor" with an index of 42.32, indicating continuous pollution, while the other sites (M2–M6) were rated as "moderate" with indices ranging from 75.25 to 75.75, indicating partial protection with some deviations from optimal standards. The results also showed that concentrations of sulfates, sodium, and chlorides exceeded the permissible limits according to the Tóth and Fitzsimmons (1962) standards, which may cause digestive disorders such as diarrhea, mineral toxicity, and imbalance of salts and fluids in the animal body. Additionally, electrical conductivity (EC) measurements at some sites exceeded the safe limits for animal consumption according to Ayers and Westcot (1989), which could negatively affect the health of ruminants and poultry. These findings underscore the urgent need to monitor pollution sources and treat water before using it for animal drinking or irrigation purposes, emphasizing the importance of further studies to identify the main sources of pollution and to develop sustainable water resource management plans in the region.